Diagnostics of Development in the System of Assessment of Educational Results of Primary School Children: from Cultural-Historical Psychology to Psychological Anthropology - Isaev, E.I.; Safronova, M.A. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2024)
The article distinguishes between pedagogical and psychological diagnostics of educational outcomes. Pedagogical diagnostics is focused on assessing the achievements of students of the planned results of mastering the educational program and has a long tradition in education. It is noted that psychological diagnostics in education is a diagnosis of the development of students in the educational process. In Russian education, the psychological diagnosis of the developmental effect of the educational program of primary general education has not been developed. L.S. Vygotsky's analysis of the main groups of theories of the relationship between learning and development and the resulting qualification of the type of diagnosis in each of the approaches to solving the problem is presented. L.S. Vygotsky's views on learning and development are investigated, and the position justified by the scientist on the initial inclusion of developmental diagnostics in school education is emphasized. The views of D.B. Elkonin on the goals and content of psychological diagnostics in developing primary education are presented. The analysis of the practice of diagnosing the general course of development of primary school children in the system of developmental education by L.V. Zankov is carried out. An anthropological approach to the diagnosis of development in education is presented. The age-normative development model of primary school children is described as the basis for the development of a system of psychological diagnostics of educational outcomes of primary general education. В статье проводится различение педагогической и психологической диагностики образовательных результатов. Педагогическая диагностика ориентирована на оценку достижений обучающимися планируемых результатов освоения образовательной программы и имеет давнюю традицию в образовании. Отмечено, что психологическая диагностика в образовании - это диагностика развития обучающихся в образовательном процессе. В отечественном образовании психологическая диагностика развивающего эффекта образовательной программы начального общего образования не разработана. Излагается анализ Л.С. Выготским основных групп теорий связи обучения и развития и вытекающего из анализа квалификация вида диагностики в каждом из подходов к решению проблемы. Исследуются взгляды Л.С. Выготского на обучение и развитие, подчеркивается обосновываемое ученым положение об изначальной включенности диагностики развития в школьное обучение. Излагаются взгляды Д.Б. Эльконина на цели и содержание психологической диагностики в развивающем начальном обучении. Проведен анализ практики диагностики общего хода развития младших школьников в системе развивающего обучения Л.В. Занкова. Представлен антропологический подход к диагностике развития в образовании. Описана возрастно-нормативная модель развития младших школьников как основа разработки системы психологической диагностики образовательных результатов начального общего образования.